Catalytic materials based on silica and alumina: Structural features and generation of surface acidity. (July 2019) - Busca, Guido
Abstract: The structural, surface chemical and catalytic properties of the materials belonging to the SiO2 Al2 O3 system are reviewed critically. In particular, amorphous silicas, transitional aluminas, different silica-aluminas (silica-rich and alumina-rich) and protonic zeolites are taken into consideration. The nature of the acid sites, of the Lewis and of the Brønsted type, over these surfaces is discussed and rationalized, based on the fundamental chemistry and structural chemistry of silicon and aluminum compounds.